Ostrowski type inequalities for functions whose second derivatives are convex generalized - Vivas Cortez, Miguel (2021)
In this presentation we introduce the notion of s - '-convex functions asgeneralization of convex functions.Some basic results under various conditions for thefunction ' are investigated. Moreover, we establish Ostrowski type inequalities for twicedifferentiable mappings which are s - '-convex.